Anaesthetic management and complications of transvascular patent ductus arteriosus occlusion in dogs. (September 2020) - Parisi, Carmelo; Phillips, Victoria; Ferreira, Jacques; Linney, Chris; Mair, Alastair
Abstract: Objective: To retrospectively analyse the anaesthetic management, complications and haemodynamic changes in a cohort of dogs undergoing transvascular patent ductus arteriosus (PDA) occlusion in a tertiary referral centre (from January 2017 to August 2018). Study design: Retrospective study. Animals: A total of 49 client-owned dogs. Methods: Anaesthetic records of dogs with PDA that underwent transvascular occlusion of the ductus were reviewed. Anaesthetic complications evaluated included tachycardia [heart rate (HR) > 160 beats minute –1 ], bradycardia (HR < 50 beats minute –1 ), hypertension [systolic arterial pressure (SAP) > 150 mmHg], hypotension [mean arterial pressure (MAP) < 60 mmHg], hypothermia (<37 °C) and the presence of arrhythmias. Cardiovascular variables [HR and invasive SAP, MAP and diastolic arterial pressure (DAP)] at the time of occlusion device deployment (time 0) were compared with variables at 5 and 10 minutes after deployment. Descriptive statistics, Shapiro–Wilk test and repeated measures analysis of variance followed by a Dunnett's post hoc test were used to analyse the data ( p < 0.05). Results: Crossbreed dogs were the most commonly represented followed by the Cavalier King Charles Spaniel. The median age was 8 (2–108) months, and female dogs were over-represented (65.3%). The most common American Society of Anesthesiologists score was III. Mean duration of anaesthesia was 96 ± 26 minutes and mean surgery time was 58 ± 21 minutes. Acepromazine with methadone was the most commonly used premedication combination (77.6%). Propofol was the most common induction agent (73.5%). General anaesthesia was maintained with isoflurane in oxygen in all dogs. Complications included hypotension (63%), hypothermia (34%), bradycardia (28%), arrhythmias (16%), hypertension (16%) and haemorrhage (2%). MAP and DAP increased significantly 10 minutes after device deployment compared with time 0. Conclusions: and clinical relevance: Hypotension was the most common complication reported in dogs undergoing transvascular PDA occlusion. No major adverse events were documented.